User-centred socio-technical requirements for telehomecare in hospital-based homecare services in Indonesia: a qualitative study - Iman Permana; Moch Zihad Islami; Winny Setyonugroho; Ika Puspita Sari; Janatarum Sri Handono; Sentagi Sesotya Utami (Intelektual Pustaka Media Utama, 2026)
The increasing number of homebound and bedridden patients in Indonesia illustrates the importance of effective hospital-based telehomecare. While telehomecare can improve access and continuity of care, its implementation depends on alignment with user needs. This study aimed to identify user-centered socio-technical requirements for telehomecare in hospital-based homecare services in Indonesia. A qualitative descriptive study was conducted using in-depth interviews and a focus group discussion with 12 purposively selected stakeholders. A telemonitoring device was used as a contextual probe. Data were analyzed using inductive thematic analysis with stakeholder triangulation. Three main areas of needs were identified: i) functional needs, which include constant monitoring, settings for specific diseases, early warning alerts, organized communication, and access to long-term data; ii) technical needs, like ease of use for older people, access through mobile devices, support for location tracking, easy-to-read dashboards, and compatibility with hospital information systems; and iii) data security, privacy, and making sure everyone can use the system, which involves dealing with. These findings help shape the design and growth of fair telehomecare systems in health settings with limited resources and provide real-world evidence from a low- and middle-income country.